17 Electronic operative notes – the way forward. (31st October 2017) - Devlin, J; Spence, D; Scoffield, J; ,
Abstract : From casual observation within the General Surgery/Regional Hepato-Biliary Unit of the Mater Infirmorum Hospital, Belfast (MIH) it was suspected that there was a wide variation in the layout, content and legibility of operation notes between all the Consultants and trainees in the Unit based upon personal preference and experience. Following a literature search we found national guidelines published by the Royal College of Surgeons that set out 20 minimum requirements for all operation notes. Using these requirements as criteria – we assessed 20 operative notes against the RCS standards aiming for 100% correlation. The comparison confirmed that there was a wide variation in the standards and content of each note. It was hypothesised that a standardised approach was necessary to improve patient care in the post-operative period so it was proposed that a trial sample of operative notes would be completed using an electronic standardised template. The templates and operative notes were completed using a single trust-wide system and, once completed and verified by the responsible Consultant, were uploaded automatically to a region-wide electronic patient database known as the Northern Ireland Electronic Care Record (NIECR). A further audit 4 months after the original cycle demonstrated that increased use of the electronic format improved the performance in the criteria that were identified as below standards in the original cycle. We anticipate that patients will benefit from this system by improving the breadth of access medical professionals have to accurate operation notes such as when dealing with delayed post-op complications that present to a different hospital or in future peri-operative surgical planning.